Evaluating the economic impacts of the technological innovation in the motor vehicle industry: The input-output approach - Hiroyuki Shibusawa; Takafumi Sugawara (European Regional Science Association (ERSA), 2010)
In this paper, the economic impacts of technological innovation, such as electric and hybrid vehicles, in the automobile industry in Japan are examined. The automobile industry has to develop environmentally friendly vehicles in the face of the global warming issue and the exhaustion problem of petroleum. The conventional automobiles with gasoline and diesel oil don't meet the demands of present age. The new generation automobiles will become popular for coming several decades. The industrial structure will be affected by the appearance of new generation automobile. Especially, since the Japanese economy strongly depends on the automobile industry, the appearance of technological innovation in the automobile industry has an influence on the other industries and the industrial regions where the automobile firms are concentrated. In this study, we explore the economic impacts of shifting the production system in the automobile industry from the conventional automobile technology to an electric and hybrid vehicle technology using the national and multiregional input-output models.
Keywords: R11; R15; R41; 330; Electric and Hybrid Vehicles; Technological Innovation; Multi-Regional Input-Output Analysis; Economic Benefits